2004
DOI: 10.1016/s1535-6108(04)00025-x
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase A is a functional target in angiogenic blood vessels

Abstract: We show that a membrane-associated protease, aminopeptidase A (APA), is upregulated and enzymatically active in blood vessels of human tumors. To gain mechanistic insight, we evaluated angiogenesis in APA null mice. We found that, although these mice develop normally, they fail to mount the expected angiogenic response to hypoxia or growth factors. We then isolated peptide inhibitors of APA from a peptide library and show that they specifically bind to and inhibit APA, suppress migration and proliferation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 37 publications
5
82
0
Order By: Relevance
“…To determine the best homing, SKLMS1 cells were incubated with targeted phage displaying one of the following: RGD-4C (10,14,15), the interleukin-11 receptor (IL11R)-targeting peptide CGRRAGGSC (21), or the aminopeptidase A (APA)-targeting peptide CPRECES (22); insertless phage and phage displaying an unrelated peptides served as negative controls. RGD-4C had the highest binding to sarcoma cell surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the best homing, SKLMS1 cells were incubated with targeted phage displaying one of the following: RGD-4C (10,14,15), the interleukin-11 receptor (IL11R)-targeting peptide CGRRAGGSC (21), or the aminopeptidase A (APA)-targeting peptide CPRECES (22); insertless phage and phage displaying an unrelated peptides served as negative controls. RGD-4C had the highest binding to sarcoma cell surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cause of the premature death in the c-Maf null mouse has not been determined, but the relatively late stage mortality indicates that c-Maf is either compensated for by another large Maf or not involved in embryonic vasculogenesis. However, pathologic angiogenesis in the adult is believed to occur via processes distinct from those of normal developmental angiogenesis (Marchio et al, 2004,Marler et al, 2002,Becker et al, 2005 and thus formation of functional embryonic vasculature in the absence of c-Maf does not preclude its critical role in angiogenesis in the adult. An endothelial-specific c-Maf null animal model will be useful for addressing this question.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutively, APN is a membrane-bound metallopeptidase that plays multiple functions as a regulator of various hormones and cytokines, protein degradation, antigen presentation, cell proliferation, cell migration, and angiogenesis (Luan and Xu, 2007;Razak and Newland, 1992;Riemann, 1999). More recently, this technique allows the identification of the sequence CPRECES, specific for another aminopeptidase, the aminopeptidase A (APA), expressed on endothelial and perivascular tumour cells (Marchio, 2004).…”
Section: B Amentioning
confidence: 99%
“…Constitutively, APN is a membrane-bound metallopeptidase that plays multiple functions as a regulator of various hormones and cytokines, protein degradation, antigen presentation, cell proliferation, cell migration, and angiogenesis (Luan and Xu, 2007;Razak and Newland, 1992;Riemann, 1999). More recently, this technique allows the identification of the sequence CPRECES, specific for another aminopeptidase, the aminopeptidase A (APA), expressed on endothelial and perivascular tumour cells (Marchio, 2004).Various compounds, including cytotoxic drugs, cytokines, antiangiogenic agents, viral particles, fluorescent and contrast tracers, DNA complexes, and other biologic response modifiers have been coupled or synthetically added to NGR peptides in order to increase their vasculature-homing effects (Arap, 1998;Buehler, 2006;Corti and Ponzoni, 2004;Curnis, 2005;Curnis, 2000;Grifman, 2001;Pastorino, 2006;Pastorino, 2003a;Zarovni, 2004).Recently, we showed that liposomes are attractive for targeting drugs and other effectors to tumour vasculature because they can carry large payloads. Using nanoparticles of doxorubicin (DOX) targeted to tumour endothelial cells by coupling the liposomes with peptides containing the NGR sequence, we evaluated their efficacy in orthotopic model of human neuroblastoma (Pastorino, 2003a).…”
mentioning
confidence: 99%
See 1 more Smart Citation